Prevalence of asymptomatic SARS-CoV-2 infection in children in Sivas province, Central Anatolia - Candan, Merve; Yıldırım, Salih (The European Research Journal, 2022)
Objectives: Transmission from asymptomatic patients is one of the biggest challenges in controlling the Coronavirus disease 2019 (COVID-19) outbreak because these cases are a potential source for disease spread. Based on this situation, the aim of our study is to determine the prevalence of COVID-19 in asymptomatic pediatric dental patients representing Sivas and surrounding provinces. Methods: The population of the study consists of pediatric patients between the ages of 0-14 who applied to Sivas Oral and Dental Health Hospital General Operating Room for dental treatments between July 2020 and August 2021. Results: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was detected in only 5 patients (approximately 1.80%) out of 278 asymptomatic pediatric patients. Conclusions: It is thought that the COVID-19 infection, which threatens the whole world, can progress asymptomatically in children, and therefore it may be a risk factor for the spread of the infection. To tackle the COVID-19 pandemic, it is recommended to maintain a high level of infection control measures in schools and day-care and to implement widespread testing on a global scale targeting the pediatric population.